Hydrolysates and bioactive peptides generated from chicken protein hydrolysis: A systematic review of antihypertensive effects in rats - Araujo, Thiago Santos (2022)
In recent years, obtaining protein hydrolysates and peptides from food proteins has been widely studied in order to better understand not only their nutritional and functional properties, but also the possibility of their use as ingredients in functional foods. It is known that many dietary proteins have, in their primary structure, peptide sequences that, when released, can be absorbed by enterocytes and modulate specific physiological functions, in addition to providing essential amino acids and contributing to energy metabolism. Therefore, this review aims to carry out a systematic review to assess the effectiveness of these bioactive compounds in controlling blood pressure in rats. In addition, the methodological quality of the published articles was evaluated. Searches in Scopus, ScienceDirect, ISI Web of Science and PubMed databases were focused on studies on the use of hydrolysates and peptides obtained from the enzymatic hydrolysis of various chicken tissues in rats. It was possible to verify that the positive antihypertensive effects were mainly dependent on the enzymatic conditions and enzymatic hydrolysis and the monitoring of vital organ functions is essential for the regulation of blood pressure. Due to their effectiveness and low cost, chicken protein hydrolysates could be an interesting alternative for biotechnology applications. Administration of hydrolysates and peptides derived from chicken proteins to spontaneously hypertensive rats (SHR) exhibit potential antihypertensive activity with likely cardiac protective effects against target organ damage.